Dipolar self-propelled matter: dynamical structures and applications in transport of passive matter - CAMPOS, Lucas de Queiroz da Costa (2016)
In this MSc. Thesis we investigate the dynamical properties of dipole-like self-propelled particles and their abilities to transport otherwise passive matter. We use Brownian Dynamics, via the Langevin equation, to model the interaction between the particles and the solvent. First, we simulated various sets of parameters, mapping the resulting structures formed by the magnetic active particles for several values of dipole moment and external field. Then, we analysed how these structures could aid in the transport of passive particles. We found that in dilute regimes, the preeminent cause of transport was the head-on collisions between active and passive particles, resulting in a large gap in the mean squared velocity of the two kinds of matter. In dense systems, we observed a freezing of the active-passive ensemble in systems with a low dipole moment, while particles with high dipolar moment could form veins in the crystal, and even separate into distinct regions. We also studied the magnetic active matter whose magnetic moment direction was orthogonal to that of its self-propulsion. We observed a new mechanism of transport arise, where the active particles would envelope and sweep the passive particles. This proved to be the most efficient method of transport of passive matter by self-propelled particles in dilute regimes, resulting in mean squared velocities six times larger than those obtained for parallel active particles.